Haplotype frequency of the loci DYS437, DYS438, DYS439, DYS460 (Y-GATA A7.1), DYS461 (Y-GATA A7.2), Y-GATA A10, Y-GATA C4 and Y-GATA H4 in the Bahia-Brazil population - Santos, M. V. (2004)
The study of the Y-chromosome is very important for forensic and population genetics. Although many populations have already been analysed, there is little data about Brazilian populations. The haplotype frequency of eight Y-STRs: DYS437, DYS438, DYS439, DYS460 (Y-GATA-A7.1), DYS461 (Y-GATA-A7.2), Y-GATA-A10, Y-GATA-C4 and Y-GATA-H4 in 72 male individuals from Bahia was established. A total of 67 different haplotypes were observed, of which 63 were unique, three were found in two individuals, and one was found in three individuals. The haplotype diversity and the capacity of discrimination for all eight Y-specific STR loci were calculated to be 98.38% and 93.06%, respectively. A mutational event in both loci DYS437 and DYS439 were found in the same individual.